Associations between weight misperception, contextual factors, and weight loss behaviours in young adult men with overweight/obesity. (2nd December 2019) - Pool, Andrew C.; Coffman, Donna L.; Sarwer, David B.; LaRose, Jessica G.; Hart, Chantelle N.
Summary: Objective: Young men are less likely to engage in weight loss behaviours than their female counterparts. This may be because of an increased likelihood for young men, particularly young black men, with overweight/obesity to misperceive their weight status. This study examined racial differences in weight status perception accuracy and associations between this perception and weight loss behaviours among young men. Associations between weight loss behaviours and contextual factors were also explored. Methods: Data from 1417 young adult (YA) men with overweight/obesity from the 2007 to 2014 National Health and Nutrition Examination Survey (NHANES) were analysed. Associations between weight status perception accuracy, contextual factors, and weight loss attempts and behaviours were examined with logistic regression. Results: YA men with overweight/obesity were more likely to report weight loss attempts and behaviours if they perceived themselves as being overweight (OR = 3.10; 95% CI, 2.18‐4.41; P < .01; OR = 3.20, 95% CI, 2.16‐4.72, P < .01, respectively). Greater education and income were associated with a greater likelihood of reporting weight loss attempts and healthy weight loss behaviours. Greater reported depressive symptoms were associated with reported weight loss attempts but not healthy weight loss behaviours. There were no differences by race for reported weight loss attempts or behaviours. Conclusion: Among YA men with overweight/obesity, perceiving oneself as overweight was associated with reporting weight loss attempts and healthy weight loss behaviours. Future research should consider how weight status perception accuracy affects weight loss attempts among YA men and what additional factors may account for racial differences.